The Aesthetic Regime of Art Between Performative Subversion and Transferential Transgression - Habjan, Jernej (Filozofski vestnik, 2016)
One of the ways Rancière’s aesthetics is being read in the hegemonic Anglo-American space is via the Anglo-American theory of the performative, which today is itself read there via Derrida. Such attribution of performativity to Rancière’s aesthetic regime of art is hence an attribution not only of performativity, but also of subversivity. This disregards not only Austin’s opposition between artistic and performative utterances, but also Rancière’s dissociation of the aesthetic regime’s heteronomous autonomy from the impossible artistic autonomy. For Austin explicitly views aesthetic utterances as etiolations of performatives (which he sees as reproducing a given distribution of the sensible), and Rancière, as the practice of suspending, not subverting, ideological practices (which he sees as including performatives). Thus, Austin proposes a negative concept of art, a positive constitution of which can be found in Rancière, who should therefore not be read with Judith Butler, from whom the attributors of performativity to the aesthetic regime borrow the notion of performativity. However, this performativist appropriation of the theory of aesthetic regime and the theory itself nonetheless make a totality, insofar as Rancière himself neglects the institutionalised field of the symbolic as a condition of political subjectivation.